Deep brain stimulation in multiple system atrophy mimicking idiopathic Parkinson's disease. - Thavanesan, N; Gillies, M; Farrell, M; Green, A; Aziz, T (Karger, 2014)
Deep brain stimulation (DBS) is approved for idiopathic Parkinson's disease (IPD) but has a poor evidence base in Parkinson-plus syndromes such as multiple system atrophy (MSA). We describe the clinical and neuropathological findings in a man who was initially diagnosed with IPD, in whom DBS was unsuccessful, and in whom MSA was unexpectedly diagnosed at a subsequent autopsy. This case report highlights that DBS is often unsuccessful in MSA and also demonstrates that MSA can masquerade as IPD, which may explain treatment failure in a small group of patients apparently suffering from Parkinson's disease. Additionally, it also presents a case with an unusually long duration of disease prior to death, comparable only to a handful of other cases in the literature.